VARIOUS PARAMETERS AFFECTING THE PRODUCTION OF DRIED TAMBAQUI (Colossoma macropomum) FILLET: Life Sciences-Food science and Technology - NGUYEN PHUOC MINH (International Journal of Life Science and Pharma Research, 2022)
Tambaqui (Colossoma macropomum) has been considered promising for fish farming in Mekong region. Tambaqui has a high output production in continental fish farming just after shrimp, catfish and tilapia. The industrial production of tambaquis for export markets is expected to increase, requiring the diversification of processed products from this fish. It’s normally sold in retail fresh or frozen, whole, or gutted. Therefore present study was conducted to identify the effect of salt soaking time, salt concentration, dry temperature and stability of the dried tambaqui filler with prerservation time. Results of present study revealed that best quality of the dried tambaqui fillet could be obtained when dried tambaqui fillet treated with 1.0% salt for 1.5 hoursand drying at 60oC to 28% moisture content. This application could preserve the dried tambaqui fillet for 9 months in PA bag without any deterioration.